MENGENAL MUSIK TRADISIONAL TALEMPONG PACIK DI MINANGKABAU - Teti Darlenis (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
Minangkabau society have several kinds of talempong ensemble music, such as Talempong Pacik, Talempong Unggan, Talempong Batu, Talempong Jao, Talempong Batuang, Talempong Sambilu, and Talempong Kayu, also other kinds of talempong. Among the ensembles, talempong pacik is the most popular It grows and is developed all over the countries, and becomes a musical identity of the society. The way ofplaying the instruments is by holding them, that ~ why it is called pacik, literally means being held. Every group of talempong ensemble have thefr own repertoire of songs, which is influenced by the back ground of the local composer And therefore it becomes the pride of the country and functions to entertain the society in ritual and social activities.Keyword:Â Talempong Pacik, interlocking technic, nagari